Selection and Evaluation of Thermo-tolerant Yeast Isolates for Sugar Tolerance - Jayamma, P.; Shirnalli, G. Geeta; Nagalakshmi, S.; Aruna, R. (International Journal of Bio-resource and Stress Management, 2024)
The experiment was carried out during October, 2020 to January, 2022 in the Department of Agricultural Microbiology, College of Agriculture, University of Agricultural Sciences, Dharwad, Karnataka, India to evaluate the ability of thermotolerant yeast strains isolated from various fruit wastes to produce ethanol. Yeast strains should be able to grow in media with a high level of sugar concentration in order to produce high levels of ethanol. An improved yeast strain that can withstand high sugar concentrations will be able to use more carbohydrates and yield more ethanol. The ability of thermotolerant yeast strains isolated from various fruit wastes to produce ethanol was studied. A total of 100 and 10 yeasts isolates were obtained from several fruit wastes and tested for thermotolerance by growing in Yeast extract dextrose peptone broth at varied temperatures, namely 35, 40, and 45°C. Among these, 20 yeast isolates were successfully grown at 35, 40, and 45°C and were identified using morphological and biochemical methods. Further all the 20 thermotolerant isolates were screened for sugar tolerance. The broth medium was supplemented with different glucose concentrations ranging from 10 to 25% (w/v) and incubated at temperature (35, 40 and 45°C), time (24, 48, 72, and 96 h) and growth was measured by OD at 600 nm. Among 20 isolates, four (YP11, YM17, YPA48 and YPA64) were tolerant to glucose at 25.0% (w/v). The objective of this research was to isolate and characterize thermotolerant and sugar tolerant yeast to optimize maximal ethanol production from fruit waste.